INFLUENCE OF SPINAL EXERCISES AS AN ADJUNCT TO CONVENTIONAL PHYSIOTHERAPY ON PAIN AND FUNCTIONAL MOBILITY IN CHRONIC KNEE OSTEOARTHRITIS - Khilwani, Amruta; Rayjade, Amrutkuvar; Nikam, Gauri; Mohite, Shraddha (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND—Knee osteoarthritis (OA) is one of the chronic problems affecting older people that causes pain and physical disability that impairs functional impairment of the knee OA patients significantly. As there is interconnection between the spine and knee, most of the patients with knee OA experience spinal muscle weakness. So the aim of the study is to reduce the pain and improve the functional mobility of participants using spinal exercises.Objectives: To compare the influence of spinal exercises as an adjunct to conventional physiotherapy on pain and functional mobility in chronic knee osteoarthritis.Method: The study was conducted at the physiotherapy outpatient department of Krishna Hospital and MRC, Karad. The sample size was 70, which was further divided into 2 groups, each containing 35 participants, by a simple consecutive sampling method. Group A was given spinal exercises along with SWD and conventional knee exercises. Group B was the control group, which was given only SWD and conventional knee exercises.STATISTICAL ANALYSIS—Data was analyzed using paired and unpaired t-tests.Result: Paired and unpaired t-tests were used for statistical analysis. In pre-intervention, there was no statistically significant difference seen in p-values for VAS, which was 0.7685; WOMAC, which was 0.3924; and SPBFU was 0.7792. On comparing the post-intervention score, the results showed an extremely significant difference was seen with p-values for VAS, WOMAC, and SPBFU, which were